Understorey bird species diversity along elevational gradients on the northern slope of Mt. Makiling, Luzon, Philippines (Asia Life Sciences : the Asian International Journal of Life Sciences, 2012)
To survey and record the understorey bird species diversity along elevational gradients on the northern slope of Mt. Makiling, Luzon, Philippines, six sampling sites with 20 netting stations were established between low forest edge up to mossy forest in the following elevational ranges (masl): 40-199 (forest edge), 200-399 (secondary lowland forest with built-up areas), 400-599 (secondary lowland forest), 600-750 (mixed grassland and forest), 751-899 (midmon